If it's not what You are looking for type in the equation solver your own equation and let us solve it.
28+9y=2(3y+5)+2(2y+5)
We move all terms to the left:
28+9y-(2(3y+5)+2(2y+5))=0
We calculate terms in parentheses: -(2(3y+5)+2(2y+5)), so:We get rid of parentheses
2(3y+5)+2(2y+5)
We multiply parentheses
6y+4y+10+10
We add all the numbers together, and all the variables
10y+20
Back to the equation:
-(10y+20)
9y-10y-20+28=0
We add all the numbers together, and all the variables
-1y+8=0
We move all terms containing y to the left, all other terms to the right
-y=-8
y=-8/-1
y=+8
| F(x)=8x/x-3 | | 2^(10-2x)=4 | | −13(p+9)=4 | | 2x/5=-18/5 | | 3/(s-2)=1/7 | | -8x-48=24-12x | | -3(-4x-5)=75 | | k/25=5 | | 2x-5=18/5 | | (4,-2);m=0.5 | | 250=(3x-5)(x) | | 4/3u=36 | | 2(3y+5)=2(2y+5) | | 4(-10-6x)=-232 | | -2(8-5x)=-46 | | 4-(3x-3)=2x-(4-x) | | -7(-5+4x)=63 | | -109-7v=-14v+17 | | 7x+2(x-7)=65 | | 5×-y=-3 | | 5/24x=10 | | 2x^2+16x-32=6 | | 2+x=6x-3 | | -6.2x+-10=-28.6 | | B+4/3=b+8/8 | | -1=k/3-4 | | 2x-9=7x-54 | | 3+7n=7+2(1+4n) | | 77+10=n | | 0.0765t^2-0.894t+1.854=0 | | 20x+30=-50 | | x-6/2=2(2x-12) |